Kesuksesan Knowledge Transfer Di Laboratorium Perguruan Tinggi Melalui Pengelompokkan Rekan Kerja Menggunakan Agent-Based Modeling And Simulation - Fadillah Ramadhan; Afrin Fauzya Rizana; R Rispianda; Yoanita Yuniati (Department Industrial Engineering, University of Muhammadiyah Malang, 2018)
One of aspect that contributes to improving organizations performance is knowledge transfer effectiveness. On the other hand, knowledge transfer is a dynamic interaction between people, process, and environment so that activity related to knowledge transfer categorized as a complex and adaptive process. The use of agent-based modeling and simulation approach is very appropriate in modeling knowledge transfer due to its ability to deal with the dynamic, complex, and adaptive process. Moreover, the agent-based approach has the ability in describing the interaction between the social agent that possess particular behavior. The purposes of this study are to identify the factors that influence the success of knowledge transfer in the university laboratory. In addition, the results show that agent-based modeling and simulation approach can determine the best scenario that can increase the success of knowledge transfer based on grouping of colleagues.